A Dynamic Mesh Study of Series and Parallel Bladder Pressure Pulsation Attenuators. Issue 3 (16th March 2021) - Xin, Qing; Zhang, Yongxiang
Abstract : To solve the problem that the attenuation effect of the bladder pressure pulsation attenuator cannot be quantitatively analysed, the dynamic mesh technology was combined with the user-defined function to calculate the serial and parallel attenuators. Overcoming the divergence problem in finite-element fluid calculation and the negative volume problem in the dynamic mesh updating process, the bladder pressure pulsation attenuator was dynamically simulated under different fluctuating frequencies and different inflatable pressures. The results show that a serial attenuator attenuates pressure pulsation better than a parallel one does, especially when the fluid fluctuation frequency is consistent with attenuator's natural frequency. And the lower the inflatable pressure of the bladder is, the better the attenuation effect is. The simulation results match the experimental results, which verifies the model's validity and practicability, and also provides a new method and idea to improve bladder attenuator's perfomance and analyse the variable boundary problem.